Anthropometric changes in non-medicated ADHD boys - Ptacek, Radek; Kuzelova, Hana; Paclt, Ivo; Zukov, Ilja; Fischer, Slavomir (Neuro endocrinology letters, 2009)
OBJECTIVES: The aim of the study is to compare complex anthropometric characteristics in non medicated boys with ADHD and normal population. METHODS: Complex anthropometric examination of non-medicated ADHD boys (n=46, average age 11.03 years), statistical and clinical comparison to the actual population growth norm. In contrast to the most of the previous studies, which analyzed mostly only BMI or basic signs of growth as height and weight, the presented study operates with a complex anthropometrical measurement and comparison with actual population norm. RESULTS: The results of the study show significant differences in the signs of nutrition (percentage of fat) and growth indicators (lower values of height) between ADHD and non ADHD children. Further anthropometrical parameters show other possible but in the studied sample statistically non-significant differences. CONCLUSION: Many studies analyzed growth relation to medication of ADHD children, but did not consider that the changes could appear also in non-medicated children and thus they might not be only a side effect of the treatment but a manifestation of the disorder itself. Growth changes in non-medicated children are not described well enough, so the presented study was performed to compare anthropometrics characteristics in ADHD boys with norm of nonclinical population and specify the differences. The results points to hypothesis that the growth changes are primarily caused by the disorder itself.
Keywords: Child; hyperkinetická porucha; průzkumy a dotazníky; Anthropometry; antropometrie; Statistics, Nonparametric; Surveys and Questionnaires; Attention Deficit Disorder with Hyperactivity; neparametrická statistika; Humans; mužské pohlaví; Male; lidé; dítě